Biogeochemical thallium cycling during a mesocosm phytoplankton spring bloom: Biotic versus abiotic drivers. (15th November 2021) - Mori, Corinna; Beck, Melanie; Hintz, Nils H.; Merder, Julian; Bunse, Carina; Dittmar, Thorsten; Dlugosch, Leon; Böttcher, Lea; Pahnke, Katharina; Striebel, Maren; Schnetger, Bernhard; Simon, Meinhard; et al.
Abstract: Thallium (Tl) is classified as a non-(bio)-essential and highly toxic element in the marine environment. Despite its active and passive involvement in bio-cycling processes, it is considered a conservative type element in open ocean settings. Previous studies on the Tl-behavior in the coastal waters of the southern North Sea, however, documented non-conservative Tl-behavior in seasonal and tidal patterns. As drivers for the non-conservative depletion, Tl-fixation in redox stratified adjacent sediments as well as its complexation with algae-bloom derived organic matter were suggested. Due to superimposition by resuspended lithogenic particles, it was not possible to distinguish whether the Tl concentration pattern was induced by biotic or abiotic processes. The main motivation of the present study was to investigate the non-conservative Tl-behavior during a phytoplankton bloom in coastal ocean water masses and to identify potential key drivers. We conducted an indoor mesocosm experiment where artificial seawater was inoculated with a natural phytoplankton and bacteria community from the southern North Sea and incubated under natural light and temperature conditions, mimicking a neritic North Sea water column. The incubation of six weeks covered the different stages of two distinct phytoplankton bloom events as well as a subsequent bacteria bloom. Our results reveal a non-conservative Tl-depletion, which seemed to be primarily caused by the coupling to algae bloom derived OM-cycling. The extent of Tl-depletion was dependent on the amount and the composition of organic matter. While the first phytoplankton bloom, dominated by Diatom-species, did not induce significant deviations of Tl from theoretical conservative behavior, especially the colonial stage (hydrogel formation) of the secondary occurring Phaeocystis sp. bloom induced significant depletions of dissolved Tl with rates up to ~27% d -1 . Global extrapolations of potential algae-induced deficits in dissolved Tl and its potential export Tl from the open water column have shown that the processes identified for Tl removal in this study could be responsible for a flux in the range of 4–20% of the total removal previously assumed in Tl mass balances. Our study emphasizes that although Tl is classified as a conservative-type element, biological processes have an impact on the global Tl budget and thus must be considered in the respective oceanographic models.